Frequent immunoglobulin G4 expression in a common variant of primary cutaneous marginal zone B‐cell lymphoma. (4th October 2017) - Sun, Jing Ru; Nong, Lin; Liu, Xiao Qing; Tu, Ping; Wang, Yang
Abstract: Immunoglobulin (Ig)G4 expression was recently observed in a proportion of primary cutaneous marginal zone B‐cell lymphoma (PCMZL) with plasmacytic differentiation. IgG4‐related disease is characterised by polyclonal lymphoplasmacytic infiltration with IgG4 expression, storiform fibrosis and obliterative phlebitis in histopathology. Here we report three cases of common variants of PCMZL with predominant and varied IgG4 expression, suggesting there is an underlying clonal progression between these two entities.